If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + -3) + -6 = 2(x + 5) + -2(2 + -4x) Reorder the terms: 12(-3 + x) + -6 = 2(x + 5) + -2(2 + -4x) (-3 * 12 + x * 12) + -6 = 2(x + 5) + -2(2 + -4x) (-36 + 12x) + -6 = 2(x + 5) + -2(2 + -4x) Reorder the terms: -36 + -6 + 12x = 2(x + 5) + -2(2 + -4x) Combine like terms: -36 + -6 = -42 -42 + 12x = 2(x + 5) + -2(2 + -4x) Reorder the terms: -42 + 12x = 2(5 + x) + -2(2 + -4x) -42 + 12x = (5 * 2 + x * 2) + -2(2 + -4x) -42 + 12x = (10 + 2x) + -2(2 + -4x) -42 + 12x = 10 + 2x + (2 * -2 + -4x * -2) -42 + 12x = 10 + 2x + (-4 + 8x) Reorder the terms: -42 + 12x = 10 + -4 + 2x + 8x Combine like terms: 10 + -4 = 6 -42 + 12x = 6 + 2x + 8x Combine like terms: 2x + 8x = 10x -42 + 12x = 6 + 10x Solving -42 + 12x = 6 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -42 + 12x + -10x = 6 + 10x + -10x Combine like terms: 12x + -10x = 2x -42 + 2x = 6 + 10x + -10x Combine like terms: 10x + -10x = 0 -42 + 2x = 6 + 0 -42 + 2x = 6 Add '42' to each side of the equation. -42 + 42 + 2x = 6 + 42 Combine like terms: -42 + 42 = 0 0 + 2x = 6 + 42 2x = 6 + 42 Combine like terms: 6 + 42 = 48 2x = 48 Divide each side by '2'. x = 24 Simplifying x = 24
| 24x+12y=60 | | X/2-17=9 | | (x^4)+(8x^3)+(20x^2)+(16x)+4=0 | | -7(x-4)+5(x+2)+2(2x-1)=0 | | -7x-22= | | 10+x=16x | | 5-3x=1/3x | | 720+4x=9x | | 31=3w+9-8w | | (6x-32)/12=x/10 | | X-8=2X-10 | | 2x-1+6(2x+1)=16x-(2x-5) | | (-2/3x^3y)^3*(-2/3x^3y)^2:(-2/3x^3y)^5 | | 4x+10y=56 | | 4/9x=10 | | 20m-18=5(3m+5)+2 | | 30+2(6x-8)=2x-(5-2x+51) | | 2x^3-5x^2-10x+1=0 | | -(6x+6)+16x=33 | | x^3-5x^2-10x+5=0 | | 21=5t^2+25t | | 1/7*Ln(x) | | 14d+9=5d+45 | | 3x/5=13 | | 9n^4-10n^2+1=0 | | 5(x-5)=-11.5 | | 3(a+5)=35.1 | | 8.3=3c-1 | | 9e-2=28.6 | | 2p=6.8 | | Y=30x+216 | | (X*X)+15=11 |